Olefin polymerization method

By using solid catalyst components containing titanium, magnesium, halogen and internal electron donor compounds during the olefin polymerization process and adding alcohol compounds, the polymerization performance of the catalyst is optimized, and the problem of how to improve the stereoregulation of the polymer and the production of high-performance polymers is solved, thereby improving the stereoregulation orientation of the catalyst and maintaining the polymerization activity.

CN119841981AActive Publication Date: 2025-04-18CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202311354555.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-18
Publication Date
2025-04-18
Estimated Expiration
2043-10-18

AI Technical Summary

Technical Problem

During the olefin polymerization process, how to optimize the polymerization performance of the catalyst to improve the stereoregulation of the polymer and the ability to produce high-performance polymers.

Method used

The solid catalyst component containing titanium, magnesium, halogen and internal electron donor compounds is used, and a small amount of alcohol compound is added during the polymerization process, combining specific solid catalyst components and cocatalyst alkylaluminum compounds, the external electron donor compound is used to form a catalyst system.

Benefits of technology

While maintaining the good comprehensive performance of the catalyst, the stereoregulation of the catalyst is improved, and the polymerization activity and hydrogen adjustment sensitivity are basically unchanged, thereby producing high-performance polymers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119841981A_ABST
    Figure CN119841981A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of olefin polymerization catalysts, and relates to an olefin polymerization method. The olefin polymerization method comprises the following steps: carrying out contact reaction on a mixture of olefin and an alcohol compound and a catalyst system; wherein the catalyst system comprises a reaction product of the following components: (1) a solid catalyst component, the solid catalyst component comprises titanium, magnesium, halogen and an internal electron donor compound; the magnesium compound is dialkoxy magnesium; (2) an aluminum alkyl compound; and (3) an external electron donor compound. According to the catalyst system, the alcohol compound is introduced in the polymerization process, under the condition that good comprehensive performance of the catalyst is kept, the stereoregularity of the catalyst is improved, the polymerization activity and the hydrogen regulation sensitivity are basically kept unchanged, and production of high-performance polymer products is facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of olefin polymerization catalysts, and in particular relates to an olefin polymerization method. Background Art

[0002] As is known to all, the catalyst system used in the homopolymerization or copolymerization of α-olefins generally consists of three parts, specifically including: (1) a main catalyst (solid catalyst component), (2) a co-catalyst (usually an alkyl aluminum compound) and (3) an external electron donor compound added during the polymerization.

[0003] It is well known to those skilled in the art to use one or more external electron donor compounds to control the stereoregularity and morphology of polymers during polymerization. In addition to affecting the stereoregularity of polymers, external electron donors often affect other aspects of catalyst performance to varying degrees.

[0004] In the process of olefin polymerization, the presence of other components besides external electron donors will have different degrees of influence on the polymerization process.

[0005] It is well known that non-propylene components in the raw material propylene will have different degrees of influence on the polymerization results. For example, the presence of a small amount of ethylene will increase the polymerization activity of the catalyst and affect the stereoregularity of the polymer. The presence of trace amounts of water and oxygen at different levels will reduce the polymerization activity of the catalyst to varying degrees and affect other properties of the catalyst.

[0006] For a specific catalyst, adding a certain amount of non-propylene components during the polymerization process to optimize the polymerization performance of the catalyst is the problem that this patent will solve. Summary of the invention

[0007] The inventors of the present invention unexpectedly discovered during their research that a solid catalyst component containing titanium, magnesium, halogen and an internal electron donor compound can obtain a polymer with excellent comprehensive properties by adding a small amount of alcohol compound to the solid catalyst component during olefin polymerization and combining it with a specific solid catalyst component under the same polymerization conditions. By adjusting the polymerization conditions, the obtained catalyst system specifically shows that the polymerization activity and hydrogen adjustment sensitivity remain basically unchanged, and the stereospecificity of the catalyst will be improved to varying degrees. Based on this discovery, the present invention is proposed.

[0008] In order to achieve the object of the present invention, the present invention provides an olefin polymerization method, comprising the following steps:

[0009] contacting the mixture of olefin and alcohol compound with the catalyst system for reaction;

[0010] Wherein, the catalyst system comprises the reaction product of the following components:

[0011] (1) a solid catalyst component, wherein the solid catalyst component comprises titanium, magnesium, halogen and an internal electron donor compound; the magnesium compound is a dialkoxymagnesium;

[0012] (2) Alkyl aluminum compounds;

[0013] (3) External electron donor compounds.

[0014] The alcohol compound introduced into the catalyst system of the present invention during the polymerization process improves the stereoregularity of the catalyst while maintaining good comprehensive performance of the catalyst, and the polymerization activity and hydrogen regulation sensitivity remain basically unchanged, which is conducive to the production of high-performance polymer products.

[0015] Other features and advantages of the present invention will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Exemplary embodiments of the present invention will be described in more detail with reference to the accompanying drawings.

[0017] Figure 1 A schematic diagram showing the effect of alcohol content on the performance of catalyst A is shown.

[0018] Figure 2 A schematic diagram showing the effect of methanol content on the performance of catalyst B is shown. DETAILED DESCRIPTION

[0019] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0020] In order to achieve the object of the present invention, the present invention provides an olefin polymerization method, comprising the following steps:

[0021] contacting the mixture of olefin and alcohol compound with the catalyst system for reaction;

[0022] Wherein, the catalyst system comprises the reaction product of the following components:

[0023] (1) a solid catalyst component, wherein the solid catalyst component comprises titanium, magnesium, halogen and an internal electron donor compound; the magnesium compound is a dialkoxymagnesium;

[0024] (2) Alkyl aluminum compounds;

[0025] (3) External electron donor compounds.

[0026] The solid catalyst component of the present invention can be prepared by: in an inert diluent, a dialkoxy magnesium carrier is contacted with a titanium compound and an internal electron donor compound to react to obtain a solid catalyst component;

[0027] According to the present invention, preferably, the alcohol compound is a linear or branched monohydric alcohol or polyhydric alcohol.

[0028] Specific alcohol compounds include: methanol, ethanol, n-propanol, n-butanol, n-pentanol, n-hexanol, n-heptanol, n-octanol, n-nonanol, n-decanol, 2-propanol, 2-butanol, 2-pentanol, 2-hexanol, 2-heptanol, 2-octanol, 2-nonanol, 2-decanol. 2-ethylbutanol, 2-ethylhexanol, 4-methyl-2-pentanol, 3,3,5-trimethylpentanol, 4-methyl-3-heptanol. Benzyl alcohol, 2-phenylethanol, 1-phenyl-1-propanol, ethylene glycol, glycerol, etc. The alcohol compound used can be a mixture of one or more alcohols.

[0029] In the present invention, the mass content of one or more alcohols in the mixture of alcohol and propylene is less than 5%, preferably less than 1%, and more preferably less than 0.1%.

[0030] In the present invention, during the polymerization process, the alcohol compound of the present invention is firstly mixed evenly with propylene, and then the solid catalyst component, the co-catalyst alkyl aluminum compound and the external electron donor are added to the propylene mixture for polymerization reaction.

[0031] In the present invention, the dialkoxy magnesium carrier is prepared by the following method: under the protection of an inert atmosphere, alcohol and metal magnesium are used as raw materials, and a reflux reaction is carried out in the presence of a halogenating agent; wherein the weight ratio of the alcohol to magnesium is 4 to 50:1; the alcohol is a linear or branched monohydric alcohol or polyhydric alcohol; the halogenating agent is selected from at least one of a halogen element and a halide, and the amount thereof is such that the molar ratio of the halogen atom to magnesium is 0.0002 to 0.2:1.

[0032] Wherein, the alcohol is preferably ethanol and 2-ethylhexanol. The halogenating agent is preferably selected from iodine and magnesium chloride.

[0033] In the present invention, the internal electron donor compound is selected from at least one of monovalent or polyvalent aliphatic carboxylic acid esters and aromatic carboxylic acid ester compounds; the internal electron donor compound is selected from, for example, benzoate, phthalate, malonate, succinate, glutarate, etc. Preferably, the internal electron donor compound is selected from ethyl benzoate, diethyl phthalate, diisobutyl phthalate, di-n-butyl phthalate, diisooctyl phthalate, di-n-octyl phthalate, diethyl malonate, dibutyl malonate, diethyl 2,3-diisopropylsuccinate, diisobutyl 2,3-diisopropylsuccinate, di-n-butyl 2,3-diisopropylsuccinate, dimethyl 2,3-diisopropylsuccinate, 2,2-dimethylsuccinate. At least one of diisobutyl amber, diisobutyl 2-ethyl-2-methylsuccinate, diethyl 2-ethyl-2-methylsuccinate, diethyl adipate, dibutyl adipate, diethyl sebacate, dibutyl sebacate, diethyl maleate, di-n-butyl maleate, diethyl naphthalene dicarboxylate, dibutyl naphthalene dicarboxylate, triethyl trimellitate, tributyl trimellitate, triethyl trimellitate, tributyl trimellitate, tetraethyl pyromellitate and tetrabutyl pyromellitate.

[0034] According to the present invention, preferably, the general formula of the titanium compound is Ti(OR w ) 4-k X' k , where R w C 1 ~C 20 wherein X' is Cl, Br or I, and k is an integer of 0-4.

[0035] According to the present invention, preferably, the titanium compound is at least one selected from titanium tetrachloride, titanium tetrabromide, titanium tetraiodide, titanium tetrabutoxide, titanium tetraethoxide, titanium triethoxide monochloride, titanium diethoxide dichloride and titanium triethoxide monochloride.

[0036] According to the present invention, in the solid catalyst component, the amount of the titanium compound used is 0.5-150 moles per mole of magnesium.

[0037] In the present invention, the general formula of the alkyl aluminum compound is AlR"' d X 1 3-d , where R'' is C l -C 8 Alkyl, X 1 is a halogen atom, 0<d≤3, when containing two or three R'', they can be the same or different. Preferably, the alkyl aluminum compound is triethyl aluminum, triisobutyl aluminum, tri-n-butyl aluminum, tri-n-hexyl aluminum, Al(nC 6 H 13 ) 3、Al(nC 8 H 17 ) 3 and AlEt 2 At least one of Cl.

[0038] Preferably, the molar ratio of aluminum in the alkyl aluminum compound to titanium in the solid catalyst component is 1-1000:1, more preferably 1-500:1.

[0039] In the present invention, the alkyl aluminum compound and the external electron donor compound may be contacted with the solid catalyst component alone or as a mixture of the two components.

[0040] According to different requirements on polymer properties, the catalyst system of the present invention can be directly used in the polymerization reaction of olefins; or it can be prepolymerized with olefins to generate a prepolymerized catalyst, and then polymerized with olefins.

[0041] In the present invention, the general formula of the olefin can be CH 2 =CH-R V , where R V is hydrogen or C 1 -C 6 Alkyl. Non-limiting examples of the olefin include: ethylene, propylene, butene, pentene, hexene, octene, 4-methyl-1-pentene. Preferably, the olefin is propylene and / or ethylene; more preferably, the olefin is propylene.

[0042] In addition, according to specific use requirements, the olefin can be polymerized in the presence of a small amount of diene.

[0043] In the present invention, the olefin polymerization reaction can be carried out in liquid phase (liquid phase monomer or monomer is dissolved in an inert solvent) or gas phase, or can be carried out under the operation of liquid phase and gas phase polymerization stage combination. Olefin polymerization reaction can be carried out according to known polymerization techniques, for example, adopt conventional technology such as slurry process, gas phase fluidized bed etc.

[0044] In the present invention, the olefin polymerization conditions include: the polymerization temperature is 0-150° C., preferably 60-90° C., and the polymerization pressure is normal pressure or higher.

[0045] The present invention will be further described below in conjunction with embodiments, but the scope of the present invention is not limited to these embodiments.

[0046] In the following examples and comparative examples:

[0047] 1) The isotactic index of a polymer is determined by the n-heptane extraction method. According to GB / T 2412-2008, 2 g of a dried polymer sample is placed in an extractor and extracted with boiling n-heptane for 6 hours. The residue is dried to a constant weight. The ratio of the obtained polymer weight (g) to 2 is the isotactic index.

[0048] 2) Polymer melt index: measured according to GB3682-2000 at 230°C and 2.16 kg load.

[0049] Preparation Examples 1 and 2 are respectively the preparation methods of the solid catalyst components of the embodiment of the present invention and the comparative example.

[0050] Preparation Example 1

[0051] Preparation of magnesium alkoxide:

[0052] The preparation method of magnesium alkoxide can be obtained by referring to the preparation methods of patent documents 200910176719.X, 201010283034.8, 201010522125.2, 201110172225.1, 201410573756.5, etc., and all the relevant contents disclosed therein are incorporated herein by reference.

[0053] Specifically, a 1L reactor equipped with a stirrer, a reflux condenser, a thermometer and a burette is fully replaced with nitrogen, 550 ml of ethanol with a water content of less than 200 ppm and 10 ml of isopropanol with a water content of less than 200 ppm are added to the reactor, 0.68 g of iodine and 0.42 g of magnesium chloride are added, the temperature is raised after stirring until the reflux temperature of the reaction system is reached, and then 32 g of magnesium powder and 90 ml of toluene are added, and the reaction is carried out until no hydrogen is discharged, and then washing, separation and drying are carried out to obtain a dialkoxy magnesium carrier.

[0054] Preparation of catalyst:

[0055] The preparation method of the catalyst can be obtained by referring to the preparation methods of patent documents 200910176719.X, 201010283034.8, 201010522125.2, 201110172225.1, 201410573756.5, etc., and all the relevant contents disclosed therein are incorporated herein by reference.

[0056] Specifically, in a 300ml reactor that has been repeatedly replaced with high-purity nitrogen, 10ml of toluene and 90ml of titanium tetrachloride are added, the temperature is lowered to -5°C, a suspension prepared by 10g of alkoxymagnesium obtained in Preparation Example 1 and 50ml of toluene is added, and then the temperature is slowly raised to 80°C, 2ml of DNBP (dibutyl phthalate) is added, the temperature is continued to be raised to 115°C, the temperature is kept constant for 2 hours, and the liquid is filtered clean. Then, a mixed solution of 120ml of titanium tetrachloride and 30ml of toluene is added, the temperature is raised to 110°C, and the mixture is stirred for 1 hour, and the treatment is repeated 3 times. The resulting solid is washed 4 times with 150ml of hexane at 60°C, the liquid is filtered off, and 10.5g of solid powder is obtained after drying, which is the solid catalyst component A.

[0057] Preparation Example 2

[0058] Preparation of catalyst:

[0059] In a 300ml glass reaction bottle, add 90ml (820mmol) of titanium tetrachloride and cool to -20°C, add 37mmol of a magnesium halide carrier (prepared according to the method disclosed in Example 1 of CN1330086A) in terms of magnesium element, then heat to 110°C, and add 0.3mmol of tributyl phosphate and 7.3mmol of 2-isopropyl-2-isopentyl-1,3-dimethoxypropane during the heating process. After maintaining at 110°C for 30min, filter out the liquid, wash twice with titanium tetrachloride, wash five times with hexane, and obtain catalyst component B for olefin polymerization after vacuum drying.

[0060] Examples 1-27 are provided to illustrate the catalyst system and olefin polymerization process of the present invention.

[0061] Examples 1-9

[0062] In a 5-liter autoclave, nitrogen gas was used to purge at 70°C for 1 hour, then the polymerization autoclave was replaced 3 times with gaseous propylene, the autoclave was closed, a set amount of hydrogen and 0.6 kg of liquid propylene and a set amount of methanol were introduced, the temperature was raised to the set temperature, and high-speed stirring was performed for 30 minutes; under nitrogen protection, 5 mL of triethylaluminum (TEAL) hexane solution (the concentration of triethylaluminum was 0.5 mmol / mL), 1 mL of methylcyclohexyldimethoxysilane (C-donor) hexane solution (the concentration of C-donor was 0.1 mmol / mL), 8 mL of anhydrous hexane and 4 mg of solid catalyst component A were introduced into the autoclave with 0.4 kg of propylene. The temperature in the autoclave was quickly raised to 70°C under stirring. After polymerization at 70°C for 1 hour, stirring was stopped, unpolymerized propylene monomer was removed, the polymer was collected, and vacuum dried at 70°C for 2 hours to obtain polypropylene.

[0063] The amount of methanol added and the polypropylene properties of the catalyst system are shown in Table 1 and Figure 1 shown.

[0064] Examples 10-18

[0065] Propylene polymerization was carried out according to the method of Example 1-9, except that the alcohol introduced during the polymerization was changed from methanol to ethanol.

[0066] The amount of ethanol added and the polypropylene properties of the catalyst system are shown in Table 1 and Figure 1 shown.

[0067] Examples 19-21

[0068] Propylene polymerization was carried out according to the method of Example 1-9, except that the alcohol introduced during the polymerization was a mixture of methanol and ethanol, wherein the ratio of methanol to ethanol was 1:1.

[0069] The amount of alcohol added, the polypropylene properties of the catalyst system, etc. are shown in Table 1.

[0070] Examples 22-24

[0071] Propylene polymerization was carried out according to the method of Example 1-9, except that the alcohol introduced during the polymerization was a mixture of methanol and ethanol, wherein the ratio of methanol to ethanol was 2:1.

[0072] The amount of alcohol added, the polypropylene properties of the catalyst system, etc. are shown in Table 1.

[0073] Examples 25-27

[0074] Propylene polymerization was carried out according to the method of Example 1-9, except that the alcohol introduced during the polymerization was a mixture of methanol and 2-ethylhexanol, wherein the ratio of methanol to ethanol was 1:1.

[0075] The amount of alcohol added, the polypropylene properties of the catalyst system, etc. are shown in Table 1.

[0076] Comparative Examples 1-11

[0077] Propylene polymerization was carried out according to the method of Examples 1-11, except that solid catalyst component B was used instead of A as the main catalyst during polymerization. The amount of methanol added and the polypropylene properties of the catalyst system are shown in Tables 1 and Figure 2 shown.

[0078] Table 1

[0079]

[0080]

[0081] It can be seen from Table 1 that, compared with Comparative Example 1, in Examples 1-27, when Catalyst A is used and an alcohol compound is added during the polymerization process, the isotactic index of the polymer is further improved, while in Comparative Examples 2-11, when Catalyst B is used and an alcohol compound is added, the isotactic index of the polymer is reduced.

[0082] The embodiments of the present invention have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and changes will be apparent to those skilled in the art without departing from the scope and spirit of the described embodiments.

[0083] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

Claims

1. An olefin polymerization method, characterized in that: The steps include: contacting the mixture of olefin and alcohol compound with the catalyst system for reaction; Wherein, the catalyst system comprises the reaction product of the following components: (1) a solid catalyst component, wherein the solid catalyst component comprises titanium, magnesium, halogen and an internal electron donor compound; the magnesium compound is a dialkoxymagnesium; (2) Alkyl aluminum compounds; (3) External electron donor compounds.

2. The olefin polymerization method according to claim 1, wherein The alcohol compound is a linear or branched monohydric alcohol or polyhydric alcohol; Preferably, the alcohol compound is selected from at least one of methanol, ethanol, n-propanol, n-butanol, n-pentanol, n-hexanol, n-heptanol, n-octanol, n-nonanol, n-decanol, 2-propanol, 2-butanol, 2-pentanol, 2-hexanol, 2-heptanol, 2-octanol, 2-nonanol, 2-decanol, 2-ethylbutanol, 2-ethylhexanol, 4-methyl-2-pentanol, 3,3,5-trimethylpentanol, 4-methyl-3-heptanol, benzyl alcohol, 2-phenylethanol, 1-phenyl-1-propanol, ethylene glycol and glycerol.

3. The olefin polymerization method according to claim 1, wherein In the mixture of olefin and alcohol compound, the mass content of alcohol is less than 5wt%, preferably less than 1wt%, and more preferably less than 0.1wt%.

4. The olefin polymerization method according to claim 1, wherein The preparation method of the dialkoxy magnesium comprises the following steps: Under the protection of an inert atmosphere, alcohol and metal magnesium are used as raw materials and reflux reaction is carried out in the presence of a halogenating agent; The weight ratio of the alcohol to metallic magnesium is 4 to 50:1; the alcohol is a linear or branched monohydric alcohol or polyhydric alcohol, preferably ethanol and / or 2-ethylhexanol; the halogenating agent is selected from at least one of a halogen element and a halide, preferably iodine and / or magnesium chloride, and the amount of the halogenating agent used makes the molar ratio of halogen atoms to magnesium be 0.0002 to 0.2:

1.

5. The olefin polymerization method according to claim 1, wherein The internal electron donor compound is selected from at least one of monovalent or polyvalent aliphatic carboxylic acid ester and aromatic carboxylic acid ester compounds; Preferably, the internal electron donor compound is selected from at least one of benzoate, phthalate, malonate, succinate and glutarate; More preferably, the internal electron donor compound is selected from ethyl benzoate, diethyl phthalate, diisobutyl phthalate, di-n-butyl phthalate, diisooctyl phthalate, di-n-octyl phthalate, diethyl malonate, dibutyl malonate, diethyl 2,3-diisopropylsuccinate, diisobutyl 2,3-diisopropylsuccinate, di-n-butyl 2,3-diisopropylsuccinate, dimethyl 2,3-diisopropylsuccinate, 2,2-dimethylsuccinate, diethyl 2,3-diisopropylsuccinate, diisobutyl 2,3-diisopropylsuccinate, dimethyl 2,3-diisopropylsuccinate, dimethyl 2,2-dimethylsuccinate, diethyl 2,3-diisopropylsuccinate, dibutyl 2,3-diisopropyl ...butyl 2,3-diisopropylsuccinate, dibutyl 2,3-diisopropylsuccinate, dibutyl 2,2-dimethylsuccinate, diethyl 2,3-diisopropylsuccinate, dibutyl 2,3-diisopropylsuccinate, dibutyl 2,3-diisopropylsuccinate, dibutyl 2,3-diisopropylsuccinate, dibutyl 2,3-diisopropylsuccinate, dibutyl 2,3 At least one of diisobutyl amber, diisobutyl 2-ethyl-2-methylsuccinate, diethyl 2-ethyl-2-methylsuccinate, diethyl adipate, dibutyl adipate, diethyl sebacate, dibutyl sebacate, diethyl maleate, di-n-butyl maleate, diethyl naphthalene dicarboxylate, dibutyl naphthalene dicarboxylate, triethyl trimellitate, tributyl trimellitate, triethyl trimellitate, tributyl trimellitate, tetraethyl pyromellitate and tetrabutyl pyromellitate.

6. The olefin polymerization method according to claim 1, wherein The general formula of the titanium compound is Ti(OR w ) 4-k X' k , where R w C1~C 20 An alkyl group, X' is Cl, Br or I, and k is an integer from 0 to 4; Preferably, the titanium compound is at least one selected from titanium tetrachloride, titanium tetrabromide, titanium tetraiodide, titanium tetrabutoxide, titanium tetraethoxide, titanium triethoxide monochloride, titanium diethoxide dichloride and titanium triethoxide monochloride; In the solid catalyst component, the amount of the titanium compound used is 0.5-150 moles per mole of magnesium.

7. The olefin polymerization method according to claim 1, wherein The general formula of the alkyl aluminum compound is AlR"' d X 1 3-d , where R'' is C l -C8 alkyl, X 1 is a halogen atom, 0<d≤3, when containing two or three R"', R"' are the same or different; Preferably, the alkyl aluminum compound is triethylaluminum, triisobutylaluminum, tri-n-butylaluminum, tri-n-hexylaluminum, Al(n-C6H 13 )3. Al(n-C8H 17 )3 and AlEt2Cl at least one; Preferably, the molar ratio of aluminum in the alkyl aluminum compound to titanium in the solid catalyst component is 1-1000:1, more preferably 1-500:

1.

8. The olefin polymerization method according to claim 1, wherein The external electron donor compound is a C-donor or a D-donor.

9. The olefin polymerization method according to claim 1, wherein The general formula of the olefin is CH2=CH-R V , where R V It is hydrogen or a C1-C6 alkyl group. Preferably, the olefin is selected from at least one of ethylene, propylene, butene, pentene, hexene, octene and 4-methyl-1-pentene; more preferably, the olefin is propylene and / or ethylene, further preferably propylene.

10. The olefin polymerization method according to claim 1, wherein The conditions of the contact reaction include: a polymerization temperature of 0-150° C., preferably 60-90° C., and a polymerization pressure of normal pressure or higher.

Citation Information

Patent Citations

  • Spherical catalyst components used for polymerization or copolymerization of olefin and its catalyst

    CN1330086A

  • Manufacturing method for propylene block copolymer

    CN106795257A

  • Olefin polymerization catalyst main body component, and preparation method thereof

    CN110283261A

  • Polypropylene resin composition for sheet formation

    JP2015000960A

  • Olefin polymerization catalyst

    JP2541957B2